Effects of plyometric training on grass surface versus concrete surface on jumping performance among volleyball athletes / Mohamad Hariff Ramlan - Ramlan, Mohamad Hariff (2017)
The purpose of this study was to determine the effect of 4 weeks plyometric training on the grass surface group and the concrete surface group on jumping ability among volleyball athletes. Twelve subjects (N = 12) were recruited. The subjects were evaluated in two types of the vertical jump which were squat jump and countermovement jump. The result of this study indicates that 4 weeks intervention showed a significant improvement between pre and post on squat jump and countermovement jump (p < 0.05) on both grass surface and concrete surface. However, in comparing the grass surface and concrete surface, there was no significant difference (p > 0.05). These findings suggest that 4 weeks of plyometric training on a grass surface and concrete surface improves vertical jump ability; squat jump and countermovement jump among volleyball athletes.